SIPAKATAU: SINERGI PANGAN LOKAL DAN AKTIVITAS FISIK UNTUK MENCEGAH PENYAKIT TIDAK MENULAR - Asikin, Hijrah; Sirajuddin; Ihsan; Fitriah (Jurnal Pengabdian Indonesia (JPI), 2026)
Non-communicable diseases (NCDs) remain a major health problem in Biringkanaya District, Makassar City, with high rates of obesity, hypertension, high cholesterol, and metabolic disorders. These problems are influenced by an unbalanced diet, low consumption of local foods, and a lack of physical activity. The SIPAKATAU (Synergy of Local Food and Physical Activity) programme was designed to address these issues through nutritional education, my plate demonstrations, physical activity, and the use of locally sourced, easily accessible food to the community. The activities were carried out over a month in Paccerakkang and Berua villages, involving 24 participants, health cadres, and the Paccerakkang community health centre. The intervention included pre-tests, interactive education, hands-on practice, physical activity monitoring, and health checks before and after the activities. The results showed an increase in knowledge from 50% to 75% in the good category, increased implementation of My Plate, and 75% of participants had sufficient physical activity. Health indicators showed improvement, particularly in cholesterol (normal levels increased from 1 to 7 individuals) and uric acid (100% normal). Blood sugar levels showed improvement, while blood pressure and nutritional status required longer-term intervention. The SIPAKATAU programme proved effective in improving community nutrition and health behaviours and is recommended as a model for community-based NCD prevention.